2009
DOI: 10.1111/j.1541-0064.2009.00264.x
|View full text |Cite
|
Sign up to set email alerts
|

Immigrants and homelessness—at risk in Canada's outer suburbs

Abstract: Homelessness is a risk for growing numbers of immigrants. Largely as a result of low incomes, newcomers are more likely than the Canadian‐born to spend over 50 percent of total household income on housing costs. Many newcomers suffer ‘hidden homelessness’. They do not use shelters and other services, but share accommodation, couch‐surf and rely on their social contacts for temporary and precarious housing. The adverse impact of low incomes on the housing experiences of Canadian newcomers is exacerbated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 16 publications
1
68
0
Order By: Relevance
“…Housing tenure is perhaps the most important variable influencing satisfaction with housing, with those owning their home being over three times more likely to be satisfied with their current home compared to those who rent (OR ¼ 3.021). Homeownership provides ontological security and allows immigrants to buy into the 'Canadian dream', although ownership may also not be affordable and reflect limited options within the rental market (Preston et al, 2009). This can seemingly improve satisfaction with housing and improve overall quality of life.…”
Section: Descriptive Statisticsmentioning
confidence: 97%
See 2 more Smart Citations
“…Housing tenure is perhaps the most important variable influencing satisfaction with housing, with those owning their home being over three times more likely to be satisfied with their current home compared to those who rent (OR ¼ 3.021). Homeownership provides ontological security and allows immigrants to buy into the 'Canadian dream', although ownership may also not be affordable and reflect limited options within the rental market (Preston et al, 2009). This can seemingly improve satisfaction with housing and improve overall quality of life.…”
Section: Descriptive Statisticsmentioning
confidence: 97%
“…Third-and perhaps most important-even the categorization scheme used in this article to examine the effects of scale (primary, secondary, and tertiary city tiers) masks intra-urban patterns and processes of housing conditions. How do housing conditions compare for those living in pre-war inner cities, post-war suburbs, and suburban municipalities (i.e., Preston et al, 2009)? And taking this one step further, are these patterns similar to or different across city tiers (e.g., perhaps those in MTV exhibit the same spatial patterning of housing conditions to those in other CMAs or CAs, when investigated at the neighbourhood scale.…”
Section: Summary and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, practice of immigrant culture, particularly, maintenance of large family structure, has also been pointed out as affecting the nature of immigrant housing experience. Subsequently, higher relative burden of housing costs in relation to low household incomes and the multi-family structures of these new immigrants generally predisposes them to crowding and hidden homelessness which makes them fall short of the core housing need standards (Preston et al 2009;Fiedler et al 2006). Immigrants' tendency to maintain such cultural practices as family structure in destination countries are also manifest in other areas of life where they maintain contact with their places of origin.…”
Section: Understanding Immigrant Housing Trajectoriesmentioning
confidence: 97%
“…In earlier research, Moore and Skaburskis (2004) found that housing affordability determined by income levels is identified as critical in influencing the geographical locations low income groups such as immigrants can opt to live. The situation of high housing prices together with immigrant economic disadvantage leaves most immigrants precariously housed and at risk of homelessness indulging in practices such as couch surfing (Fiedler et al 2006;Preston et al 2009). Additionally, existing subtle discriminatory rental practices towards visible minority immigrants further influences immigrant housing careers.…”
Section: Understanding Immigrant Housing Trajectoriesmentioning
confidence: 98%